The Effect of Multiple Representation-Based Learning (MRL) to Increase Studentsâ€™ Understanding of Chemical Bonding Concepts (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study was conducted to determine the effectiveness of multiple representation-based learning (MRL) model compared to discovery learning (DL) model and problem based learning (PBL) model in terms of studentsâ€™ initial abilities. The factorial design was used in this study. The selection of samples in this study was done through a random sampling technique. Three X classes of the same school was chosen. The three classes applied different learning model. The first class employed the MRL, the second class used the DL model, and the last class adopted the PBL model. Overall, the number of samples involved in the study was 117 students. The results of the study showed that the conceptual understanding of students learning using MRL was significantly different from students learning to use problem-based learning with significant differences in N-gain was 0.0004, but not significantly different from students using discovery learning. This finding showed that MRL is the most effective model for increasing the conceptual understanding of students with â€œlowâ€ and â€œmoderateâ€ initial ability compared to PBL and DL.